Pengaruh Independensi, Profesionalisme, Skeptisme Profesional, Etika Profesi dan Gender Terhadap Kualitas Audit Pada KAP di Bali - Rahayu, Ni Kadek Sri; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2020)
This study aims to determine the effect of professionalism and gender professionalism independence on audit quality at public accounting firms in Bali. Data collection methods in this study used a questionnaire. The population in this study are all auditors who work at the Public Accounting Firm in Bali with a total of 78 auditors overall. The analysis technique used is Multiple Linear Regression. Based on the analysis and testing of hypotheses, the conclusion is that (1) independence has a positive effect on audit quality, (2) professionalism has a positive effect on audit quality, (3) professional skepticism has a positive effect on audit quality, (4) professional ethics has a positive effect on quality audit (5) gender negatively influences audit quality. Keywords : Independence; Professionalism; Ethics; Gender; Audit Quality.